INFLUENCE OF THE TRANSMISSION PROCESSES UPON THE BACKGROUND BRIGHTNESS AND RELATION BETWEEN THE DARK AND BACKGROUND SCINTILLATIONS OF ELECTRO – OPTIC TRANSFORMER - Zhekov, Zhivko; Mardirossian, Garo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The background brightness is a parameter which is defined by the thermo-electronic system of the photo cathode and the level of the external influences – auto electronic and auto ionic emission, ionizations and stimulation of atoms from remaining gases, optic reverse relation screen – photo cathode, etc. Evaluation of the influence of the above mentioned processes is defined when examining the amplitudes and temporary spectres of the scintillations on the electro – optic transformer screen. The relation between the multi – electronic scintillations and the process of ionization exchange and ionization of the atoms, absorbed by the electrostatic lens under the influence of the electronic field shows a sudden increase of one or two times of the background brightness which is defined on account of the auto electronic emission.